Hermite-Hadamard-Fejér Inequality Related to Generalized Convex Functions via Fractional Integrals - M. Rostamian Delavar; S. Mohammadi Aslani; M. De La Sen (Journal of Mathematics)
This paper deals with Hermite-Hadamard-Fejér inequality for (η1,η2)-convex functions via fractional integrals. Some mid-point and trapezoid type inequalities related to Hermite-Hadamard inequality when the absolute value of derivative of considered function is (η1,η2)-convex functions are obtained. Furthermore, a refinement for classic Hermite-Hadamard inequality via fractional integrals is given when a positive (η1,η2)-convex function is increasing.